Caracterização e influência da brisa do rio Tapajós sobre dados meteorológicos na Floresta Nacional do Tapajós - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The present study emphasizes the importance of research on the processes that occur in the Atmospheric Boundary Layer (CLA) in the Amazon region, specifically in the low Tapajós region, taking into account the Tapajós River Breeze (TRB) process. In order to understand the characterization of the local circulation and mechanisms of operation of the TRB, data were used of the networks of stations, towers, satellite and also observation campaigns in the low troposphere. In order to verify the influence of the breeze on the Tapajós National Forest (TNF), the zonal component of the wind was analyzed to classify days with and without occurrence of TRB, as well as the comparison of those days on the Km67 site measurements. The results point to the occurrence of almost 50% of days with BRT on TNF, and that it presents a diurnal cycle that can reach on average 20 Km of extension and up to about 1 Km in height. The occurrence of TRB was related to the di
Keywords: Brisa do rio Tapajós; Umidade; Temperatura; Radiação; Fluxo de massa e energia; CNPQ::CIÊNCIAS EXATAS E DA TERRA; IMPACTOS AMBIENTAIS E SOCIAIS DA MUDANÇA DO USO DA TERRA NA AMAZÔNIA